Counseling on the Importance of IVA Test for Early Detection of Cervical Cancer at Posyandu - Ketut Sumidawat, Ni; Mustarin, Yanti (Lembaga Penelitian dan Pengabdian Masyarakat,Politeknik Sandi Karsa, 2023)
Cervical cancer is a significant global health problem, especially in females. Early detection of cervical cancer is essential in reducing mortality from this disease. Visual Inspection with Acetic Acid (IVA) Test is an effective and affordable method to detect precancerous changes in the cervix. Knowledge of IVA tests and access to them can be challenging, especially in community environments such as Posyandu. Various strategies have been proposed to increase public understanding and awareness of the IVA Test. This includes training Posyandu cadres, socialization at Posyandu meetings, live demonstrations, and awareness campaigns. Partnerships with local health centres are also crucial for regular IVA Test services. By integrating these efforts, it is hoped that the public will be more aware of the importance of IVA tests for early detection of cervical cancer and have better access to this service. Doing so can increase the chances of early detection, reduce mortality from cervical cancer, and protect women's overall health